The effect of therapeutic potential and safety of bone marrow-derived against adipose-derived mesenchymal stem cells in aged mice associated with septic arthritis - Alani Mohanad Khalid Ahmed; Mujahid Khalaf Ali; Basma Kh. Alani (PLoS ONE, 2025)
Mesenchymal stem cells (MSCs) show potential for treating septic arthritis in aged populations, but their efficacy and safety in aged patients remain unclear. The objective of this study is to evaluate the therapeutic potential and safety profiles of bone marrow-derived MSCs (BM-MSCs) and adipose-derived MSCs (AD-MSCs) in aged murine model of septic arthritis. MSCs were isolated, characterized, and labeled for in vivo tracking. The experiment consisted of a total of 36 mice, which included 9 subgroups with four replicates per treated group: control group, treated groups (BM-MSC1, BM-MSC2, AD-MSC1, and AD-MSC2), and untreated groups (Un-BM1, Un-BM2, Un-AD1, and Un-AD2). The treated groups received MSC therapy following the induction of septic arthritis via intra-articular injection of Staphylococcus aureus . The results showed that BM-MSC1 significantly performed higher than AD-MSCs in reducing inflammation, promoting cartilage repair, and modulating immune responses. BM-MSC1 showed significant upregulation of regenerative markers such as interleukin-10 (IL-10) and collagen type II alpha 1 chain (COL2A1) and downregulation of pro-inflammatory markers such as tumor necrosis factor-alpha (TNF-a) and matrix metalloproteinase-13 (MMP-13). Imaging confirmed superior retention, engraftment, and host tissue interaction for BM-MSCs. AD-MSCs showed slightly lower efficacy and safety, highlighting the need for optimization. Untreated groups experienced severe inflammation, tissue degradation, and systemic organ damage, emphasizing the significance of intervention. The study had identified BM-MSC1 as a superior therapeutic option for septic arthritis in elderly populations and suggested AD-MSCs as an alternative in cases where extraction is not feasible. Future research can optimize MSC therapies, explore alternative sources, and conduct translational studies. Targeted preconditioning, combinatory approaches, and advanced molecular analyses are crucial for maximizing therapeutic outcomes.